National, longitudinal NASCITA birth cohort study: prevalence of overweight at 12 months of age in children born healthy - Antonio Clavenna; Massimo Cartabia; Maurizio Bonati; Federico Marchetti; Giorgio Tamburlini; Antonio Addis; Michele Valente; Rita Campi; Stefania Manetti; Valeria Carraro; Sergio Conti Nibali; Renato Sansone; et al. (BMJ Publishing Group, 2023)
Objective To estimate the prevalence of overweight at 12 months in an Italian birth cohort and to identify factors related to an increased likelihood of being overweight.Methods The Italian NASCITA birth cohort was analysed. Infants were classified as underweight (<5th), normal weight (5-84th) and overweight (≥85th centile) at 12 months of age according to the WHO percentiles of body mass index (BMI) and the prevalence of overweight was estimated. To test the association between the chance of being overweight and parental and newborn characteristics, and infant feeding, healthy newborns (no preterm/low birth weight and with no malformations), with appropriate-for-gestational-age birth weight were selected, and univariate and multivariate analyses were performed.Results The prevalence of overweight was 23.5% (95% CI 22.2% to 24.8%) in all cohort members with 12-month data (N=4270), and 23.1% in the appropriate-for-gestational age subsample (N=2835).A big infant appetite (OR 3.92, 95% CI 2.40 to 6.40) and living in southern Italy (OR 1.58, 95% CI 1.29 to 1.94) were the main variables associated with a greater likelihood of being overweight. Breastfeeding practice did not influence the chance of being overweight, but was associated with an increase (exclusive breast feeding for at least 6 months) or a decrease (breast feeding for at least 12 months) in BMI z score at 12 months.Conclusions The sociodemographic factors (eg, area of residence, maternal employment status) seem to be the most relevant determinants influencing the chance of being overweight at 12 months. Early interventions, with particular attention to vulnerable families, may be helpful in preventing childhood and adult obesity.